Ask questions and get helpful answers.

Q.1 Prove the following identities:-

(i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx

(ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩

1 answer

  1. without brackets the first one is much too ambiguous to attempt.

    even the second one, I will fix so it works

    LS = (1+cotx+tanx)(sinx-cosx)/(sec^3x-cosec^3x)
    = (1 + cosx/sinx + sinx/cosx)(sinx-cosx)/(sec^3x-cosec^3x)
    = sinx - cosx + cosx - cos^2x + sin^2x - sinx)/(1/cos^3x - 1/sin^3x)
    = ((sin^2x/cosx - cos^2x/sinx)/((sin^3x - cos^3x)/(sin^3xcos^3x))
    = (sin^3x - cos^3x)/(sinxcosx) (sin^3xcos^3x)/(sin^3-cos^3x)
    = sin^2xcos^2x

    = RS

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.